Virtual Screening of Syzygium cumini (L.) Skeels Flavonoid Compounds as SARS-CoV-2 Main Protease Therapy Candidates - Himyatul Hidayah; Ruswanto Ruswanto; Desri Lestari; Surya Amal; Neni Sri Gunarti (Jurnal Kimia Sains dan Aplikasi, 2024)
In December 2019, the first COVID-19 cases were in Wuhan, China. This case is a global concern and a threat to public health. Based on previous research using molecular docking methods, it was found that flavonoids exhibit strong inhibitory activity in SARS-CoV-2 main proteases. The study aims to determine the flavonoid compound Syzygium cumini (L.) Skeels can interact with the SARS-CoV-2 main protease receptor and can be used as a candidate for COVID-19 therapy with virtual screening. Myricetin 4”-O-acetyl-2-O-gallate has the lowest Gibbs free energy (ΔG) of -9.82 kcal/mol. The molecular dynamics of the best compound, Myrcetin 4-O-acetyl-2-O-gallate, RMSD, and RSMF values are quite stable. As a result of pharmacokinetic prediction and toxicity, the best compounds have a relatively good pharmacokinetic profile and are non-toxic. Thus, it can be concluded that the compound Myricetin 4”-O-acetyl-2-o-gallate in the Syzygium cumini (L.) Skeels is predicted to interact with the SARS-CoV-2 main protease receptor (7C6S) as a potential drug candidate for COVID-19 therapy.